Unrolling, projecting, and stretching of curved surfaces into a plane - Berk, Sandi (Geodetski vestnik, 1999)
Problems of representing curved surfaces on thr plane are discussed. From a set of captured points, a wire frame of the surface can be created using the Delaunay triangulation. In this way, the curved surface is approximated by small planar facets. A method of stretching of the wire frame of the surface onto a plane is presented. The stretching is performed in such a manner that the sum of squares of linear distortions throughout the frame, as a whole, reaches a minimum value. The idea comes from the Airy's criterion for the projection of minimal distortions.
Keywords: geodezija; kartografija; metode; projekcije